Factoring is the process of splitting an algebraic expression into a product of simpler expressions.
Step 1 :
Find the greatest common divisor (or GCD) of the terms in an expression.
Step 2 :
Divide each term of the expression by the greatest common divisor.
Step 2 :
Write the greatest common divisor found in step 1 and result of step 2 as a product.
Factor each of the following.
Example 1 :
4x + 24y
Solution :
Greatest common divisor of 4x and 24y is 4.
Divide 4x and 24y by 4. The results are x and 6y.
4x + 24y = 4(x + 6y)
Example 2 :
2x2 – 8x
Solution :
GCD of 2x2 and 8x is 2x.
Divide 2x2 and 8x by 2x. The results x and 4.
2x2 – 8x = 2x(x - 4)
Example 3 :
x2 – 3x
Solution :
GCD of x2 and 3x is x.
Divide x2 and 3x by x. The results x and 3.
x2 – 3x = x(x - 3)
Example 4 :
3a + 6ab + 9a2
Solution :
GCD of 3a, 6ab and 9a2 is 1, 2b and 3a.
3a + 6ab + 9a2 = 3a(1 + 2b + 3a)
Example 5 :
ab + bc - 2b
Solution :
GCD of ab, bc and 2b is b.
Divide ab, bc and 2b by b. The results are a, c and -2.
ab + bc - 2b = b(a + c – 2)
Example 6 :
3(x – 6) + d(x – 6)
Solution :
GCD of 3(x – 6) and d(x – 6) is (x - 6).
Divide 3(x – 6) and d(x – 6) by (x - 6). The results are 3 and d.
3(x – 6) + d(x – 6) = (x – 6)(3 + d)
Example 7 :
2x(x + 4) + 3x + 12
Solution :
In the expression above, GCD of 3x and 12 is 3.
Divide 3x and 12 by 3. The results are x and 4.
2x(x + 4) + 3x + 12 = 2x(x + 4) + 3(x + 4)
GCD of 2x(x + 4) and 3(x + 4) is (x + 4).
Divide 2x(x + 4) and 3(x + 4) by (x + 4). The results are 2x and 3.
2x(x + 4) + 3x + 12 = (x + 4)(2x + 3)
Example 8 :
4x2y3 + 6x3y2
Solution :
GCD of 4x2y3 + 6x3y2 is 2x2y2.
Divide 4x2y3 and 6x3y2 is 2x2y2. The results are 2y and 3x.
4x2y3 + 6x3y2 = 2xy(2x + 3y)
Factoring Quadratic Expressions :
Consider the quadratic expression ax2 + bx + c.
Step 1 :
When a = 1, find a pair of factors for 'c' such that the product of factors is equal to 'c' and sum is equal to 'b'.
When a ≠ 1, multiply 'a' and 'c'. Now find a pair of factors for 'ac' such that the product factors is equal to 'ac' and sum is equal to 'b'.
Step 2 :
Split 'bx' into two terms using the factors found in step 1 and factor the expression completely.
Example 9 :
x2 + 5x + 6
Solution :
Find two factors of +6 such that the product is +6 and sum is +5.
Then the two factors of +6 are +2 and +3.
Split 5x into two terms using the factors +2 and +3.
x2 + 5x + 6 = x2 + 2x + 3x + 6
= x(x + 2) + 3(x + 2)
= (x + 2)(x + 3)
Example 10 :
x2 - 15x + 56
Solution :
Find two factors of +56 such that the product is 56 and sum is -15.
Then the two factors of -15 are -7 and -8.
Split -15x into two terms using the factors -7 and -8.
x2 - 15x + 56 = x2 - 7x - 8x + 56
= x(x - 7) - 8(x - 7)
= (x - 7)(x - 8)
Example 11 :
x2 + 2x - 15
Solution :
Find two factors of -15 such that the product is -15 and sum is +2.
Then the two factors of -15 are -3 and +5.
Split -2x into two terms using the factors -3 and +5.
x2 + 2x - 15 = x2 - 3x + 5x - 15
= x(x - 3) + 5(x - 3)
= (x - 3)(x + 5)
Example 12 :
x2 - x - 20
Solution :
Find two factors of -20 such that the product is -20 and sum is -1.
Then the two factors of -20 are -5 and +4.
Split -x into two terms using the factors -5 and +4.
x2 - x - 20 = x2 - 5x + 4x - 20
= x(x - 5) + 4(x - 5)
= (x - 5)(x + 4)
Example 13 :
2x2 + 9x + 9
Solution :
The product of 2 and 9 is +18.
Find two factors of +18 such that the product is +18 and sum is +9.
Then the two factors of +18 are +3 and +6.
Split 9x into two terms using the factors +3 and +6.
2x2 + 9x + 9 = 2x2 + 3x + 6x + 9
= x(2x + 3) + 3(2x + 3)
= (2x + 3)(x + 3)
Example 14 :
3x2 + x - 4
Solution :
The product of 3 and -4 is -12.
Find two factors of -12 such that the product is -12 and sum is +1.
Then the two factors of -12 are -3 and +4.
Split +x into two terms using the factors -3 and +4.
3x2 + x - 4 = 3x2 - 3x + 4x - 4
= 3x(x - 1) + 4(x - 1)
= (x - 1)(3x + 4)
Factoring Expressions Using Algebraic Identities :
a2 + 2ab + b2 = (a + b)2 or (a + b)(a + b)
a2 - 2ab + b2 = (a - b)2 or (a - b)(a - b)
a2 - b2 = (a + b)(a - b)
Example 15 :
x2 + 8x + 16
Solution :
x2 + 8x + 16 = x2 + 2(x)(4) + 42
= (x + 4)2
= (x + 4)(x + 4)
Example 16 :
x2 + 6xy + 9y2
Solution :
x2 + 6xy + 9y2 = x2 + 2(x)(3y) + (3y)2
= (x + 3y)2
= (x + 3y)(x + 3y)
Example 17 :
4a2 - 20ab + 25b2
Solution :
4a2 - 20ab + 25b2 = 22a2 - 20ab + 52b2
= (2a)2 - 20ab + (5b)2
= (2a)2 - 2(2a)(5b) + (5b)2
= (2a - 5b)2
= (2a - 5b)(2a - 5b)
Problem 18 :
9m2 - 16n2
Solution :
9m2 - 16y2 = 32m2 - 42n2
= (3m)2 - (4n2)
= (3m + 4n)(3m - 4n)
Problem 19 :
a2b2 - c2d2
Solution :
a2b2 - c2d2 = (ab)2 - (cd)2
= (ab + cd)(ab - cd)
Problem 20 :
x4 - y4
Solution :
x4 - y4 = (x2)2 - (y2)2
Let a = x2 and b = y2.
= a2 - b2
= (a + b)(a - b)
Substitute a = x2 and b = y2.
= (x2 + y2)(x2 - y2)
= (x2 + y2)(x + y)(x - y)
Factoring Cubic Expressions :
Step 1 :
Find the greatest common divisor (or GCD) of the two terms and the next two terms.
Step 2 :
Divide each of the first two terms by their GCD and the same with the next two terms.
Step 2 :
Write the greatest common divisors found in step 1 and results of step 2 as products and factor completely.
Example 21 :
x3 + 3x2 + 6x + 18
Solution :
GCD of x3 and 3x2 is x2.
Divide x3 and 3x2 by x2. The results are x and 3.
Similarly GCD of 6x and 18 is 6
Divide 6x and 18 by 6. The results are x and 3.
x3 + 3x2 + 6x + 18 = x2(x + 3) + 6(x + 3)
= (x + 3)(x2 + 6)
Example 22 :
x3 + 2x2 - 9x - 18
Solution :
GCD of x3 and 2x2 is x2.
Divide x3 and 2x2 by x2. The results are x and 2.
Similarly GCD of -9x and -18 is -9
Divide -9x and -18 by -9. The results are x and 2.
x3 + 2x2 - 9x - 18 = x2(x + 2) - 9(x + 2)
= (x + 2)(x2 - 9)
= (x + 2)(x2 - 32)
= (x + 2)(x + 3)(x - 3)
Apart from the stuff given above, if you need any other stuff in math, please use our google custom search here.
Kindly mail your feedback to v4formath@gmail.com
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
Jan 09, 25 01:09 PM
Jan 08, 25 04:36 AM
Jan 07, 25 03:55 AM